PENCAPAIAN TARGET LEVERAGE MELALUI SPEED OF ADJUSTMENT KARAKTERISTIK PERUSAHAAN - Yasir Maulana; Ayus Ahmad Yusuf (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2019)
This paper aims to determine the effect of company characteristics on target leverage with the relation of the speed of adjustment to target leverage. The speed of adjustment is examined to complete the analysis of the concept of dynamic capital structure in Indonesia. The characteristics of the companies studied are profitability, company size, company growth, industry, tangibility, inflation and the deficit and financial surplus of companies in the property, real estate and construction sectors listed on the Indonesia Stock Exchange in 2008 to 2015. The results of this study show that property, real estate, and construction sector companies are significantly implementing leverage targets. The data also shows that there is a significant effect of speed of adjustment to the leverage target which is faster when the company has a financial surplus compared to when the financial deficit.